PENGARUH MODAL SOSIAL DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU DIMEDIASI PERILAKU KEWARGAAN ORGANISASIONAL (STUDI KASUS GURU SMP NEGERI DI KECAMATAN JUWANA) - Hartatik, Murni Dwi; Fauzan, Mohammad (Jurnal Ilmiah Telaah Manajemen, 2019)
This study was intended to determine and analyze the influence of social capital and emotiointelligence on teacher performance that mediated by organizational citizenship behavior. The population of study was all PNS Teachers in State Junior High Schools in Juwana District as many as 149. Data testtechniques used validity test, reliability test, classic assumption test, regression analysis, and mediation test. results showed that social capital is proved having a positive effect on organizational citizenship behavior, as was emotional intelligence has a positive effect on organizational citizenship behavior. In the second regressionsocial capital has a positive effect on teacher performance but the indirect relationship is smaller than the dirrelationship so that organizational citizenship behavior does not mediate social capital on teacher performanceaddition, this study also shows that emotional intelligence has no effect on teacher performance but emotiointelligence will be more effective in influencing teacher performance when mediated by organizational citizensbehavior. Key word : Social Capital, Emotional Intelligence, Organizational Citizenship Behavior and Teach Performance.